2016
DOI: 10.1002/2211-5463.12060
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of copper homeostasis genes reveals coordinated upregulation of SLC31A1,SCO1, and COX11 in colorectal cancer

Abstract: Copper homeostasis and distribution is strictly regulated by a network of transporters and intracellular chaperones encoded by a group of genes collectively known as copper homeostasis genes ( CHG s). In this work, analysis of The Cancer Genome Atlas database for somatic point mutations in colorectal cancer revealed that inactivating mutations are absent or extremely rare in CHG s. Using oligonucleotide microarrays, we found a strong increase in mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 46 publications
3
66
0
Order By: Relevance
“…19 Total RNA was extracted from tissue and cell lines using RNeasy Mini Kit (cat no. 19 Total RNA was extracted from tissue and cell lines using RNeasy Mini Kit (cat no.…”
Section: Rna Extraction and Transcriptomementioning
confidence: 99%
See 1 more Smart Citation
“…19 Total RNA was extracted from tissue and cell lines using RNeasy Mini Kit (cat no. 19 Total RNA was extracted from tissue and cell lines using RNeasy Mini Kit (cat no.…”
Section: Rna Extraction and Transcriptomementioning
confidence: 99%
“…14 There are a growing number of studies that report the involvement of ZnTs and ZIPs in a wide variety of cancers. [16][17][18][19] At this time, no study has been undertaken to analyse the global expression of the zinc transporters in colorectal cancer (CRC) and the current study was designed to determine the expression profile of all zinc efflux and influx transporters, respectively SLC30A1 to SLC30A10 and SLC39A1 to SLC39A14 in CRC samples. 15 It is very useful to explore quantitative and qualitative differences characterizing the genetic alterations and biochemical processes in the tumor cells, the application of genome-wide technologies, microarrays, and high throughput sequencing.…”
mentioning
confidence: 99%
“…Disruption in pathways that transport copper can cause major damages in the form of metallostasis found in tumors 45 . The pathway is regulated by copper homeostasis genes and recent transcriptome analysis of copper homeostasis genes have shown the upregulation of SLC31A1, SCO and COX11 in colorectal cancer cases 46 .…”
Section: Sco1-wnt10b-x Combinationsmentioning
confidence: 99%
“…If the chain is blocked then all the intermediates on the substrate side of the block become more reduced, while all those on the oxygen side become more oxidised. 46 . It has been shown that human SCO1 and SCO2 have independent cooperative functions in copper delivery to cytochrome c oxidase (CcO) 47 , 48 & 49 .…”
mentioning
confidence: 99%
“…Human cancer cell line was plated in 96-well plates "Nunclon TM Microwell TM" (Nunc) and were incubated at 37 ∘ C. MTT assay was performed as reported by Barresi et al [37]. After 24 h, cells were treated with the compounds (final concentration 0.01-100 M).…”
Section: Treatment With Antitumor Agents and Mtt Colorimetricmentioning
confidence: 99%